Occurrence of supergene nickel ores in the Ha Tri Massive, Hoa An District, Cao Bang Province - Pho, Nguyen Van; Xuan, Pham Tich; Dang, Pham Thanh (Vietnam Journal of Earth Sciences, 2018)
Nickel (Ni) laterites are regolith materials derived from ultramafic rocks and play an important role in the world's Ni production. Ni-laterite deposits are the supergene enrichment of Ni formed from the intense chemical and mechanical weathering of ultramafic parental rocks. In Vietnam, the weathering profile containing Ni laterite was first discovered in the Ha Tri massive (Cao Bang). This profile develops on the Ha Tri serpentinized peridotite rocks classified to the Cao Bang mafic-ultramafic complex (North Vietnam) and exhibits thick weathered zone (10 - 15m). This work carried out a detailed study of the weathering profile at the center of Ha Tri massive. Samples from different horizons of the profile were collected and analyzed in detail by XRF, XRD and SEM-EDX methods to establish the relationship between the Ni-rich supergene products and the parental peridotites (lherzolite) rocks in Ha Tri massive. The results show that the saprolite horizon is most Ni-rich in the weathering profile in Ha Tri. In this horizon, Ni-silicate minerals of garnierite group such as pimelite, nepouite and other Mg-Ni silicates have been found. The appearance of minerals of garnierite group is due to the exchange of Mg by Ni during weathering of peridotite minerals, especially olivine, which leads to the enrichment of the supergene Ni. The occurrence of Ni silicates suggests the existence of the supergene Ni ore in the weathering profile of the Ha Tri massive.References Bosio N.J., Hurst J.V., Smith R.L., 1975. Nickelliferousnontronite, a 15 Å garnierite, at Niquelandia, Goias Brazil. Clays Clay Miner., 23, 400-403. Brand N.W., Butt C.R.M., Elias M., 1998. Nickel Laterites: Classification and features. AGSO Journal of Australian Geology & Geophysics, 17(4), 81-88. Bricker O.P., Nesbitt H.W. and Gunter W.D., 1973. The stability of talc. American Mineralogist, 58, 64-72. Brindley G.W. and Hang P.T., 1973. The nature of garnierites. Structures, chemical composition and color characteristics. Clay and Clay Minerals, 21, 27-40. Brindley G.W. and Maksimovic Z., 1974. The nature and nomenclature of hydrous nickel-containing silicates. Clay Minerals, 10, 271-277. Brindley G.W. and Wan H.M., 1975. Composition structures and thermal behavior of nickel containing minerals in thelizardite-ne´pouite series. American Mineralogist, 60, 863-871. Brindley G.W., Bish D.L. and Wan H.M., 1979. Compositions, structures and properties of nickel containing minerals in the kerolite-pimelite series. American Mineralogist, 64, 615-625. Cluzel D. and Vigier B., 2008. Syntectonic mobility of supergene nickel ores from New Caledonia (Southwest Pacific). Evidence from faulted regolith and garnierite veins. Resource Geology, 58, 161-170. Colin F., Nahon D., Trescases J.J., Melfi A.J., 1990. Lateritic weathering of pyroxenites at Niquelandia, Goais, Brazil: The supergene behavior ofnickel: Economic Geology, 85, 1010-1023. Das S.K., Sahoo R.K., Muralidhar J., Nayak B.K., 1999. Mineralogy and geochemistry of profilesthrough lateritic nickel deposits at Kansa,Sukinda, Orissa. Joural of Geoogical. SocietyIndia, 53, 649-668. Decarreau A., Colin F., Herbillon A., Manceau A., Nahon D., Paquet H., Trauth-Badaud D.,Trescases J.J., 1987. Domain segregation in NiFe-Mg-Smectites. Clay Minerals, 35, 1-10. Freyssinet P., Butt C.R.M. and Morris R.C., 2005. Oreforming processes related to lateritic weathering. Economic Geology, 100th aniversary volume, 681-722.Garnier J., Quantin C., Martins E.S., Becquer T., 2006. Solid speciation and availability of chromium in ultramafic soils from Niquelandia, Brazil. Journal of Geochemical Exploration, 88, 206-209. Garnier J., Quantin C., Guimarães E., Becquer T., 2008. Can chromite weathering be a source of Cr in soils? Mineralogy Magazine, 72, 49-53. Gleeson S.A., Butt C.R. and Elias M., 2003. Nickel laterites: A review. SEG Newsletter, 54, 11-18. Gleeson S.A., Butt C.R., Wlias M., 2003. Nickellaterites: a review. SEG Newsletter, Society of Economic Geology, 54. Available from www.segweb.org. Golightly J.P., 1981. Nickeliferous laterite deposits. Economic Geology, 75th Anniversary volume, 710-735. Golightly J.P., 2010. Progress in understanding the evolution of nickel laterite. Society of Economic Geology, In Special Publication, 15, 451-485. Manceau A. and Calas G., 1985. Heterogeneous distribution of nickel in hydrous silicates from New Caledonia ore deposits. American Mineralogist, 70, 549-558. Nguyen Van Pho, 2013. Tropic weathering in Vietnam (in Vietnamese). Pubisher Science and Technology, 365p.Ngo Xuan Thanh, Tran Thanh Hai, Nguyen Hoang, Vu Quang Lan, S. Kwon, Tetsumaru Itaya, M. Santosh, 2014. Backarc mafic-ultramafic magmatism in Northeastern Vietnam and its regional tectonic significance. Journal of Asian Earth Sciences, 90, 45-60.Pelletier B., 1983. Localisation du nickel dans les minerais ‘‘garnieritiques’’ de Nouvelle-Caledonie. Sciences Ge´ologique: Me´moires, 73, 173-183.Pelletier B., 1996. Serpentines in nickel silicate ores from New Caledonia. In Grimsey E.J., and Neuss I. (eds): Nickel ’96, Australasian Institute of Miningand Metallurgy, Melbourne, Publication Series 6(9), 197-205. Proenza J.A., Lewis J.F., Galı´ S., Tauler E., Labrador M., Melgarejo J.C., Longo F. and Bloise G., 2008. Garnierite mineralization from Falcondo Ni-laterite deposit (Dominican Republic). Macla, 9, 197-198. Soler J.M., Cama J., Galı´ S., Mele´ndez W., Ramı´rez, A., andEstanga, J., 2008. Composition and dissolution kinetics ofgarnierite from the Loma de Hierro Ni-laterite deposit,Venezuela. Chemical Geology, 249, 191-202. Springer G., 1974. Compositional and structural variations ingarnierites. The Canadian Mineralogist, 12, 381-388. Springer G., 1976. Falcondoite, nickel analogue of sepiolite. The Canadian Mineralogist, 14, 407-409.Svetlitskaya T.V., Tolstykh N.D., Izokh A.E., Phuong Ngo Thi, 2015. PGE geochemical constraints on the origin of the Ni-Cu-PGE sulfide mineralization in the Suoi Cun intrusion, Cao Bang province,  Northeastern Vietnam. Miner Petrol, 109, 161-180.Tran Trong Hoa, Izokh A.E., Polyakov G.V., Borisenko A.S., Tran Tuan Anh, Balykin P.A., Ngo Thi Phuong, Rudnev S.N., Vu Van Van, Bui An Nien, 2008. Permo-Triassic magmatism and metallogeny of Northern Vietnam in relation to the Emeishan plume. Russ. Geol. Geophys., 49, 480-491.Trescases J.J., 1975. L'évolution supergene des roches ultrabasiques en zone tropicale: Formation de gisements nikelifères de Nouvelle Caledonie. Editions ORSTOM, Paris, 259p.Tri T.V., Khuc V. (eds), 2011. Geology and Earth Resources of Vietnam. Publishing House for Science and Technology, 645p (in English). Villanova-de-Benavent C., Proenza J.A., GalíS., Tauler E., Lewis J.F. and Longo F., 2011. Talc- and serpentine-like ‘‘garnierites’’ in the Falcondo Ni-laterite deposit, Dominican Republic. ‘Let’s talk ore deposits’, 11th Biennial Meeting SGA 2011, Antofagasta, Chile, 3p.Wells M.A., 2003. Goronickel laterite deposit. New Caledonia. CRC LEME, p.3.